"Some voluntarily and some under pressure": Conceptualization, reasons, attitudes, and consequences of sexting among adolescents. (December 2022) - Ojeda, Mónica; Dodaj, Arta; Sesar, Kristina; Del Rey, Rosario
Highlights: Considering adolescents' reported experience brings important nuances on sexting. Consensual and non-consensual sexting cannot be understood in the same way. Sexual gratification and pressure are equally frequent reasons for sending sexting. Harming and ending a relationship are the most frequent reasons for forwarding. Adolescents have a high awareness of the consequences, both positive and negative. Abstract: Sexting has become another form of intimate communication in the digital society in which we live, not only for adults but also for adolescents. Therefore, this study aims to explore adolescents' perspectives on the definition of sexting, reasons for engaging, or not, in it, attitudes towards this phenomenon and its possible consequences. Focus groups conducted with 57 adolescents aged 15–19 in Bosnia and Herzegovina and Croatia highlight sexting as a complex phenomenon in which consent is central to understanding it. Adolescents point to sexual gratification and pressure as the most frequent reasons for sending erotic-sexual content, and harming another person and ending a relationship as the most frequent reasons for forwarding without consent. Most of the attitudes reported towards sexting are rejectionist or neutral but, in fact, they are in line with the logic of positive attitudes. Moreover, they denote a high awareness of the possible consequences, both positive and negative. These findings substantially expand knowledge for addressing sexting in psychoeducational programmes by considering the perspective and experience of adolescents' own voice.